Globalization and Firm Performance - Luis A. V. Cat\~ao; Pedro de Faria; António Martins; Miguel Portela (Institute of Labor Economics (IZA), 2023)
Using a new panel dataset of about 140 thousand Portuguese firms during 2006-2019, we measure the effects of globalization on firm-level performance along four dimensions: ownership of capital, employment of foreign-seasoned managers, and participation in export and import markets. Once at least one of these channels is active, firms are larger, less leveraged, employ better qualified workers, and pay higher hourly wages. We also uncover a pecking order of effects, with export-market participation having generally larger positive effects on productivity and negative effects on unit labor costs. All four channels interact, sometimes complementing, sometimes substituting one another. For instance, foreign ownership boosts exports at the extensive margin while being an importer and/or having a foreign-experienced manager help at the intensive margin; conversely, the marginal productivity gains of foreign-ownership are greatly reduced when the firm is already an exporter. Breaking down the effects of each channel by firm size, we show that smaller firms stand the most to gain from export market participation and foreign-ownership.
Keywords: D22; D24; F23; G34; J3; L20; M10; 330; foreign direct investment; entrepreneurship; trade; productivity; wages; labor costs; leverage; firm size distribution